(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
In this article studied the features of renal blood flow in patients with gestational age obstructive pyelonephritis. The features of the excretory function of the kidneys in gestational pyelonephritis and hydronephrosis before and after restoration of urodynamics of the upper urinary tract were determined. Particular attention is paid to the pathogenetic validity of the sanitation of the renal cavity system and their subsequent internal drainage in the complex treatment of gestational age obstructive pyelonephritis.